Media Coverage of Edward Snowden in 2013 and 2014 - Wendratama Engelbertus (IPTEK-KOM : Jurnal Ilmu Pengetahuan dan Teknologi Komunikasi, 2014)
Whistleblowing has been acknowledged as an important contributor to government transparency and the watchdog function of the press. However, there has long been a tension between the U.S. government and its employees who decide to blow the whistle. The relationship between the U.S. government and whistleblowers is as complicated as the relationship between national security and the American press. This study explored howthe image of Edward Snowden, who revealed the extensive use of  Americans’ surveillance in National Security Agency, was covered in ten different websites from 2013 to 2014. Snowden’s image appeared to be more positively viewed with the passage of time.Keywords: whistleblowing, national security, Edward Snowden, NSA surveillance programs